Penyuluhan Pergaulan Remaja Zaman Millenial Ditinjau Dari Aspek Agama Islam - Nelli Novyarni; Imelda Aprileny; Muhammad Anhar; Sumitro; Maserih (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
This activity provides an overview of how students form good friendships (connections) from an Islamic perspective, provides an overview of the negative effects of promiscuity among young people (millennials), It helps (millennials) develop good personality traits around teenagers (millennials) to provide an overview and help combat the easy reception of negative information. The methods used in this activity consist of advising on the unification of millennial youth from aspects of Islam using unification materials provided by Resource People. Participants will provide material and advice through Q&A afterwards. Participants in this activity were students from Diponegoro Vocational School in Rawamanggung, East Jakarta. Her 1st grade through her 3rd grade students that we teach will be asked to represent each grade, for a total of 51 students. This is because it is very important to provide these students with insight into good character development by actively participating in consultation.